2012
DOI: 10.14419/ijamr.v1i4.160
|View full text |Cite
|
Sign up to set email alerts
|

Hyers-Ulam Stability of Linear and Nonlinear Differential Equations of Second Order

Abstract: In this paper we established the Hyers-Ulam stability of a nonlinear differential equation of second order with initial condition. We also proved the Hyers -Ulam stability of a linear differential equation of second order with initial condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Proof. Suppose that z ∈ C 2 (I), such that |z (t)| ≤ |z(t)| and satisfies the inequality (14) with initial condition (4). From the Theorem 2 it follows that (20) has the Hyers-Ulam-Rassias stability with initial condition (19) and according to the substitution in Lemma 3 it follows that (5) has the Hyers-Ulam-Rassias stability with initial condition (4).…”
Section: Hyers-ulam-rassias Stability Of the Nonlinear Differential Ementioning
confidence: 94%
“…Proof. Suppose that z ∈ C 2 (I), such that |z (t)| ≤ |z(t)| and satisfies the inequality (14) with initial condition (4). From the Theorem 2 it follows that (20) has the Hyers-Ulam-Rassias stability with initial condition (19) and according to the substitution in Lemma 3 it follows that (5) has the Hyers-Ulam-Rassias stability with initial condition (4).…”
Section: Hyers-ulam-rassias Stability Of the Nonlinear Differential Ementioning
confidence: 94%
“…In [19] Brillouët-Belluot indicated that there are only few outcomes of which we could say that they concern nonstability of functional equations. However in [20]…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, numerous papers on Hyers-Ulam stability have been published, especially in ordinary differential equations (ODEs) [4][5][6][7][8]. There are fruitful results in ODEs, including linear and nonlinear equations.…”
Section: Introductionmentioning
confidence: 99%